Short review on the synthetic routes for the antiepileptic drug (S)-levetiracetam - Paul, Sayantan; Bhattacharya, Asish K. (Organic Process Research and Development, 2024)
Epilepsy is a chronic disorder characterized by recurrent unpredictable seizures. Levetiracetam (Keppra) was introduced by UCB for the treatment of partial onset seizures in patients above 16 years of age diagnosed with epilepsy. This review reports synthetic strategies available for the synthesis of (S)-levetiracetam and will certainly aid the quest for the development of new routes for its synthesis.
Keywords: antiepileptic drug; butyrolactam; epilepsy; levetiracetam; synthesis